Beyond the DSM: trends in psychiatry diagnoses (Archives of Clinical Psychiatry, 2017)
Background: Although widely used in clinical practice and research, Diagnostic and Statistical Manual of Mental Disorders (DSM) diagnoses have low validity: patients with different mental disorders can share similar symptoms, while those with the same diagnosis might have different symptoms. In fact, the DSM diagnostic system has been considered one of the main obstacles for further development of psychiatric research. Recently, it has been proposed that psychiatry nosology should be reframed according to a biologically-based etiology. Objectives: To review present and past endeavors of establishing an etiology-based nosology. Methods: Comprehensive review of articles on the topic. Results: From Hippocrates onwards, multiple attempts have been undertaken aiming to move etiology and nosology closer. The most recent efforts are represented by Developmental Psychopathology (DP) and the Research Domain Criteria (RDoC), which presents an operational matrix recommended to be used in clinical research instead of the DSM diagnoses. Discussion: The DSM-based nosology is faulty. RDoC and DP might be interesting alternatives for an etiology-based nosology. However, while DP has already brought promising results, RDoC is a novel proposal, whose advantages and disadvantages should gradually be identified in the upcoming years.